Tele-entomology and tele-parasitology: A citizen science-based approach for surveillance and control of Chagas disease in Venezuela - Delgado-Noguera, Lourdes A.; Hernández-Pereira, Carlos E.; Ramírez, Juan David; Hernández, Carolina; Velasquez-Ortíz, Natalia; Clavijo, José; Ayala, Jose Manuel; Forero-Peña, David; Marquez, Marilianna; Suarez, Maria J.; Traviezo-Valles, Luis; Escalona, Maria Alejandra; et al. (Parasite epidemiology and control, 2022)
Chagas Disease (CD), a chronic infection caused by the Trypanosoma cruzi parasite, is a Neglected Tropical Disease endemic to Latin America. With a re-emergence in Venezuela during the past two decades, the spread of CD has proved susceptible to, and inhibitable by a digital, real-time surveillance system effectuated by Citizen Scientists in communities throughout the country. The #TraeTuChipo (#BringYourKissingBug) campaign implemented in January 2020, has served as such a strategy counting on community engagement to define the current ecological distribution of CD vectors despite the absence of a functional national surveillance program. This pilot campaign collected data through online surveys, social media platforms, and/or telephone text messages. A total of 79 triatomine bugs were reported from eighteen Venezuelan states; 67 bugs were identified as Panstrongylus geniculatus, 1 as Rhodnius pictipes, 1 as Triatoma dimidiata, and 10 as Triatoma maculata. We analyzed 8 triatomine feces samples spotted from 4 Panstrongylus geniculatus which were confirmed positive by qPCR for T. cruzi . Further molecular characterization of discrete typing units (DTUs), revealed that all samples contained TcI, the most highly diverse and broadly distributed strain of T. cruzi. Moreover, analysis of the mitochondrial 12S gene revealed Myotis keaysi, Homo sapiens, and Gallus gallus as the main triatomine feeding sources. This study highlights a novel Citizen Science approach which may help improve the surveillance systems for CD in endemic countries.Chagas Disease (CD), a chronic infection caused by the Trypanosoma cruzi parasite, is a Neglected Tropical Disease endemic to Latin America. With a re-emergence in Venezuela during the past two decades, the spread of CD has proved susceptible to, and inhibitable by a digital, real-time surveillance system effectuated by Citizen Scientists in communities throughout the country. The #TraeTuChipo (#BringYourKissingBug) campaign implemented in January 2020, has served as such a strategy counting on community engagement to define the current ecological distribution of CD vectors despite the absence of a functional national surveillance program. This pilot campaign collected data through online surveys, social media platforms, and/or telephone text messages. A total of 79 triatomine bugs were reported from eighteen Venezuelan states; 67 bugs were identified as Panstrongylus geniculatus, 1 as Rhodnius pictipes, 1 as Triatoma dimidiata, and 10 as Triatoma maculata. We analyzed 8 triatomine feces samples spotted from 4 Panstrongylus geniculatus which were confirmed positive by qPCR for T. cruzi . Further molecular characterization of discrete typing units (DTUs), revealed that all samples contained TcI, the most highly diverse and broadly distributed strain of T. cruzi. Moreover, analysis of the mitochondrial 12S gene revealed Myotis keaysi, Homo sapiens, and Gallus gallus as the main triatomine feeding sources. This study highlights a novel Citizen Science approach which may help improve the surveillance systems for CD in endemic countries.